Siiwollisuuden tuntoa ja ylewätä kauneuden mieltä : suomenkielinen nuorisokirjallisuus 1851-1899 - Kuivasmäki, Riitta (1990)
This study examines the corpus of Finnish-language children's literature published in Finland during the latter half of the nineteenth century (1851-1899) within the theoretical framework of literary history, sociology, and reception theories. Before the mid-nineteenth century there had appeared only 101 Finnish and Swedish books for children and the youth. Most of these titles were secular and spiritual didactic literature. The actual "secular" Finnish-language children's literature developed later and more or less simultaneously with so-called adult literature. It did not lag very far behind the international development. A central force in the birth of Finnish children's literature was Fennomania, the nationalist movement awakened by J.V. Snellman, and its ideology of public enlightenment. It was supported both by the school and library establishments and by an increasingly complex network of societies and associations. Z. Topelius set an example with his own production and manifestos. Models were also searched for in world literature; e.g. many classical works were first translated into Finnish as adaptations for the youth. Translations accounted for over 80 % of the children's literature produced between 1851 and 1899 (including reprints), with the total number of titles already standing at 1000 or more. The most typical genre in original Finnish-language children's literature - as in children's literature elsewhere - was short prose fiction, i.e. stories and fairy tales (folk tales); the rise of the youth novel took place in the 1890s. Numerous anthologies, periodicals, poetry books and songbooks also belong to the early stage of our children's literature. The chief task of literature was to adapt our rising youth to the Christian and patriotic cultural ideology of the time and at the same time to introduce Finland among the civilized nations. The whole body of cultural activists in our country, the Fennomanian clergymen, teachers, journalists and members of various cultural associations were all working for this important end - to raise in each of them (in Eero Salmelainen's words) "a chaste mind with a noble longing for beauty".